Push and pull factors associated with the consumption of women’s professional basketball games: A canonical correlation analysis - Min, Sophia D.; Zhang, James J.; Byon, Kevin K. (Frontiers in Psychology, 2022)
The purpose of this study was to empirically investigate the interrelationships between push and pull factors associated with the consumption of women’s professional basketball games. Multiple factors pertaining to sport consumers’ internal needs, identified as “push” factors, contain various intangible socio-psychological motivations representing an individual’s intrinsic desires that drive consumers towards certain goal-driven behaviors. On the other hand, “pull” factors, related to the supply side, refer to the different aspects of sport products the management of sport teams provides. It is imperative to obtain a better understanding of the push-pull interaction so that sport marketers can design their products to satisfy spectators’ expectations with different needs. Spectators (N=628) attending WNBA games responded to an on-site survey. CFA was conducted to ensure the psychometric properties of the scales, which showed that the overall model fit the data well. A canonical correlation analysis was performed, and two significant functions were revealed by the dimension reduction analysis. The first function (I-Want-Everything-Consumer) suggests that the market segment comprises individuals with multiple needs and expectations, both of which need to be met simultaneously. Thus, sports marketers can satisfy WNBA consumers' needs by enhancing the quality of tangible pull factors. The second function (Achievement-Seekers) revealed that the consumers motivated by vicarious achievement expect game promotion rather than the quality of the opposing team, indicating that sport marketers should provide tailored promotional strategies to satisfy this segment of consumers. This study provides empirical evidence of the relationship between WNBA consumers’ multiple needs and attributes associated with WNBA core product. As such, successful marketing strategies should be developed by incorporating the critical push and pull factors pertaining to WNBA games.